Contribution to the knowledge of early geotechnics during the 20th century: Laurits Bjerrum - G. Guillán-Llorente; B. Muñoz-Medina; A. Lara-Galera; R. Galindo-Aires (History of Geo- and Space Sciences)
The founder of soil mechanics, Karl Terzaghi, took the initiative in 1954 to contact the Danish engineer Laurits Bjerrum, requesting to meet. Terzaghi wanted to meet the engineer who had written a paper on the stability of the unusual Norwegian quick clays at the European Slope Congress in Stockholm. Bjerrum was 36 years old at the time, had a PhD and was already director of the NGI (Norges Geotekniske Institutt – Norwegian Geotechnical Institute). From his position as director of the NGI, he was actively involved in many varied consultancies, placing great value on the continuous interaction between practice and research. Bjerrum's strategy for establishing the NGI came from the experience of other research centres such as the BRS (Building Research Station) in Great Britain and Imperial College London. In addition, having lived through the Nazi occupation of Denmark, he was predisposed to be against the misuse of authority and established an open structure for the institute from its inception. Bjerrum was in close contact with the Norwegian Institution of Technology, and, in 1952, he succeeded in getting soil mechanics incorporated as a compulsory subject in the civil engineering degree. Subsequently, in 1960, the Chair of Soil Mechanics and Foundation Engineering was established. The first laboratory of this chair was equipped with material donated by the NGI. Bjerrum died young (54 years old), but he had built an excellent reputation through his work at the NGI and his contributions to international conferences, where he maintained a close relationship with the significant figures in geotechnics: Terzaghi, Skempton, Peck and Casagrande. He made regular trips to the USA, where he was a visiting professor at MIT (Massachusetts Institute of Technology) and received the highest international decorations.